5-HT3 receptor antagonists for the prevention of perioperative shivering undergoing spinal anaesthesia: a systematic review and meta-analysis of randomised controlled trials. Issue 10 (5th October 2020) - Shen, Qi-Hong; Li, Hui-Fang; Zhou, Xuyan; Lu, Yaping; Yuan, Xiao-Zong
Abstract : Objective: Perioperative shivering (POS) is a common complication in patients undergoing spinal anaesthesia. The present study investigated the efficacy of 5-HT3 receptor antagonists in preventing POS following spinal anaesthesia. Design: Systematic review and meta-analysis. Data sources: Pubmed, Embase, the Web of Science and Cochrane Library were searched from database establishment on 31 July 2019. Eligibility criteria: Randomised controlled trials that reported the effects of 5-HT3 receptor antagonists in the prevention of POS in patients after spinal anaesthesia. Data extraction and synthesis: Two reviewers independently extracted data. The primary outcome of the present study was the incidence of POS. The risk of bias for the included studies was assessed according to the Cochrane Handbook. The quality of primary outcome was evaluated by Grading of Recommendations Assessment, Development and Evaluation. Trial sequential analysis for the primary outcome was performed to reduce the type 1 error caused by repeated meta-analysis and the required information size was calculated. Results: A total of 13 randomised controlled trials consisting of 1139 patients were included. The overall incidence of POS was significantly lower in the 5-HT3 receptor antagonists group (risk ratio 0.31; 95% CI 0.26 to 0.38; p<0.01; I 2 =0%). Subgroup analysis for different types of 5-HT3 receptor antagonists and timing of administration produced similar results. Also, patients had a lower incidence of postoperative nausea and vomiting after administrating 5-HT3 receptor antagonists. No statistically significant differences in drug-related adverse effects were observed. Grading of Recommendations Assessment, Development and Evaluation revealed a high level of evidence. The cumulative z-curve crossed the trial sequential monitoring boundary. Conclusions: The present study revealed that prophylactic 5-HT3 receptor antagonists were an effective measure for reducing the incidence of POS in patients after spinal anaesthesia. However, further studies investigating the different types of surgeries are required. PROSPERO registration number: CRD42019148191.